Development of CORE Model-Based Mathematics Learning Videos For Grade VI Students at SDN 1 Kaba-Kaba - Suardani, Ni Putu; Sesara Ariyana, I Komang; Harja Subrata, Gede; Mastiningsih, Ni Nyoman; Windayani, Ni Luh Ika (Metta : Jurnal Ilmu Multidisiplin, 2023)
Media is helpful in providing meaningful learning activities through the application of the CORE (Connecting, Organizing, Reflecting, and Extending) model as a learning video scenario. This study aimed to determine the build design of the CORE model-based mathematics learning video and to determine the feasibility of the CORE model-based mathematics learning video for sphere material for sixth-grade students at SDN 1 Kaba Kaba. Media design used the ADDIE model (ADDIE (analyze, design, development, implementation, evaluation) as a step in the product development process. The study did not use a population or sample but used test subjects learning content experts, learning design experts, learning media experts, and grade VI students at SDN 1 Kaba Kaba. Data collection method used was a questionnaire method, observation, and interviews. The research data results were analyzed using a quantitative descriptive method by looking for the eligibility percentage in the learning process through the trial results. Thus, it generated learning video products, including as follows. There were design descriptions of the CORE model-based mathematics learning video development with stages of analysis, design, development, and evaluation. CORE model-based learning videos based on product trial results, including as follows. The assessment results of learning content experts with the acquisition of very good qualification percentage score (95.20%); the assessment results of the learning design expert with the acquisition of very good qualification percentage score (90.55%); the assessment results of the learning media experts with the acquisition of very good qualification percentage score  (95.54%); and the student assessment results through individual trials obtained very good qualification percentage score (90.35%). Based on the trial results, it can be concluded that CORE model-based learning videos were feasible to use in the learning process.